2005
DOI: 10.1097/00149831-200512000-00007
|View full text |Cite
|
Sign up to set email alerts
|

GlObal Secondary Prevention strategiEs to Limit event recurrence after myocardial infarction: the GOSPEL study. A trial from the Italian Cardiac Rehabilitation Network: rationale and design

Abstract: The GOSPEL trial, the rationale and design of which we present here, was designed to test a new strategy of secondary prevention delivery and to raise standards of long-term secondary prevention in Italy. With a cohort of over 3200 patients, GOSPEL is the largest randomized, multifactorial lifestyle and risk factor intervention trial after myocardial infarction conducted so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
155
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(171 citation statements)
references
References 15 publications
7
155
2
7
Order By: Relevance
“…Excluding the by far largest trial by Giannuzzi et al [16] from meta-analysis yielded slightly larger differences at 4 to 6 and 8 to 12 months but a non-significant negative effect at 18 to 24 months. Egger's test indicated significant (p=0.048) funnel plot asymmetry; when the trial by Giannuzzi et al [16] was excluded, the test became non-significant (p=0.43). The intensity of the intervention and study quality (lower risk of bias) did not have a major influence on study findings (Table 5).…”
Section: Study Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Excluding the by far largest trial by Giannuzzi et al [16] from meta-analysis yielded slightly larger differences at 4 to 6 and 8 to 12 months but a non-significant negative effect at 18 to 24 months. Egger's test indicated significant (p=0.048) funnel plot asymmetry; when the trial by Giannuzzi et al [16] was excluded, the test became non-significant (p=0.43). The intensity of the intervention and study quality (lower risk of bias) did not have a major influence on study findings (Table 5).…”
Section: Study Resultsmentioning
confidence: 82%
“…Seven [13,22,25,30,40,41,44] of the 13 trials testing lifestyle interventions with moderate or high intensity and three [16,20,35] of the 13 trials with low or very low intensity interventions reported significant improvement in self-reported risk behavior regarding to at least two of the three key aspects of diet, physical activity, and stress management.…”
Section: Study Resultsmentioning
confidence: 99%
See 3 more Smart Citations